ANALYSIS OF THE CONTENT OF EXERCISE SEVENTH GRADE ENGLISH TEXTBOOK - Sjafty Nursitti NP Maili; Endang Sondari (Universitas Putera Batam, 2020)
The aim of this study was to analyze the content of exercise in the English textbook appropriate with the criteria a good exercise or activity in the English textbook purposed by expert theory. This study is a qualitative research which the data was obtained with observation and documentation; First, Interview, researcher asked English teacher to answer the questions; Second, documentation, data was taken based on the main English textbook used SMP Muhammadiyah Cawang 4 Jakarta Timur namely Buku Bahasa Inggris untuk SMP/MTS Kelas VII by Erlina, S and Muhammad, H published Mediatama. In the English textbook there were 24 exercises. The result of this research shows that the exercises of this book provided from 24 exercises which were six exercises without new vocabulary students to communicate and five exercises do not incorporate by pair/group work, so the exercise do not meet criteria with a good exercise in the English textbook, but the English teacher always give the supplementary material that taken from other media sources